Pengenalan Integrasi Budaya dan Matematika Melalui Media Edukasi 3D Puzzle Bola Ugi’ - Suandi, Ahmad Yusuf; Putri Akhmad, Ummu Qalsum; ., Nurjannah; Lubis, Nurlatifah; Yudha, Muh. Reza Eka; Areni, Intan Sari (Faculty of Engineering UNHAS, 2023)
Mathematics often becomes a less favored subject among elementary school students, including those at Inpres Borongrappo Elementary School in Gowa Regency, which is our partner in this Community Service activity. To address this issue, we have innovated by introducing an engaging learning medium in the form of a 3D miniature puzzle Bola Ugi’ implemented using the Realistic Mathematics Education (RME) method. This educational program aims not only to enhance students' curiosity and creativity but also to sharpen their motor coordination skills. The educational program primarily focuses on creating two-dimensional shapes from cardboard, calculating the volume of three-dimensional objects, and exploring the cultural significance of 'mappatettong bola' and 'mappalette bola.' Additionally, students assemble and color the 3D puzzle Bola Ugi’. The evaluation of activities in the form of a questionnaire to determine students' interest in learning mathematics and becoming acquainted with culture, as well as test models to determine students' level of understanding of mathematics and culture, which are administered before (pre-test) and after (pre-test) the educational program, respectively. The questionnaire results revealed that 16 students were more excited about learning mathematics and 15 students were more enthusiastic about learning about culture. Meanwhile, the exam results reveal a considerable increase in the number of correct responses in each question, indicating that the instruction increased pupils' comprehension of mathematics and culture. The educational program employing the 3D puzzle Bola Ugi’ as learning method significantly enhances motivation and comprehension of mathematics, as evidenced by the improved test scores and questionnaire responses.